Analysis of the Effectiveness of the My Tirtanadi Application as a Community Service Solution (Case Study : PDAM TIRTANADI) - Salsabila Putri; Muhammad Yafiz (Penerbit Jurnal Indonesia, 2022)
Service is one of the important factors that can be prioritized by the regional drinking water company (PDAM) TIRTANADI Tuasan branch to the entire community to obtain maximum satisfaction. Before or before the online application became a comparison by the community, which used to be difficult in registration and payment activities, now it can be accessed from home only via Android. The purpose of this study is to analyze how the effectiveness of the my tirtanadi application on payments made by the community. The method used in this research is descriptive qualitative in the form of interviews and observations. The results of this study are the ineffectiveness of the my tirtanadi application in the convenience of the community, because the application often has errors and lacks complete menus or options to meet customer needs.